(untitled) (Research, Society and Development, 2021)
Shear bond strength between resin cement and lithium disilicate ceramics after different etching protocols, different heat treatments, and intrinsic staining was tested. Lithium disilicate specimens were 10 mm long by 5 mm wide by 2 mm thick and were divided into 5 groups (n=10): Group 1: specimens heated to 840 ºC; Group 2: specimens submitted to double heating treatment (heated to 840 ºC, cooled down, heated to 770 ºC); Group 3: specimens heated to 840 ºC, cooled down, intrinsically stained, heated to 770 ºC; Group 4: specimens heated to 840 ºC, cooled down, heated to 800 ºC; Group 5: specimens heated to 840 ºC, cooled down, intrinsically stained, heated to 800 ºC. Groups 1, 3, and 5 were etched with 10% hydrofluoric acid (HF) and analyzed by scanning electron microscopy (SEM) at 10,000´. Specimens from groups 2 and 4 were not etched with HF. Energy dispersive spectrometry (EDS) and SEM analyzed specimen staining physicochemical changes in groups 3 and 5. The resin cement samples were 1-mm in diameter and 2-mm in height. Analysis of variance and independent t test were used to compare the groups in the study (p<0.05). Different lithium disilicate surface and heat treatments changed specimen topography. No significant effect was found in the adhesion between intrinsically stained lithium disilicate specimens and resin cement (p>0.05). Shear bond strength between resin cement and lithium disilicate ceramics was not influenced by intrinsic staining. Topography of the ceramic material changed with different heating temperatures and with acid etching.